A study on evaluation of stress intensity factor (KI) and J‐integral for 40Ni2Cr1Mo28 alloy (structural steel): analytical and finite element analysis approach. Issue 12 (14th December 2022) - Mohan Kumar, S.; Rajesh Kannan, A.; Pramod, R.; Siva Shanmugam, N.; Dhinakaran, V.; Krishnaveni, A.
Abstract: Defects like crack are common in engineering structures that are either material intrinsic or initiate during fabrication. The theory of fracture mechanics establishes a mechanistic relationship between the maximum allowable loads applied on a structural component to the size and location of an actual or assumed crack in the component. Linear‐elastic or complex elastic‐plastic, i. e., non‐linear models, are used to conduct the fracture analysis. Established studies show that methods of non‐linear fracture mechanics, in comparison to elastic methods, offer more accurate measures of the fracture behaviour in failed structures with high toughness and materials with low strength. In this work, an attempt is made to evaluate stress intensity factor‐ KI and J ‐integral of 40Ni2Cr1Mo28 alloy (structural application steel) for various crack length‐a to width ratio‐W (a/W = 0.25, 0.375, 0.5, 0.625 and 0.75) against the applied force in the form of load under plane stress condition by elasto‐plastic finite element analysis (compact tension specimen). Non‐linearity is modeled using the inverse Ramberg‐Osgood relation. Compact tension specimen is modeled in ANSYS software and analyzed by using Finite element analysis. It is found that there is a good agreement between both finite element analysis and theoretical value with an error deviation in the range of 0 % to 6 %. Abstract : This research work aims to analyze and calculate the stress intensity factor ( KI ) and J‐integral of 40Ni2Cr1Mo28 alloy (structural application steel) for various crack length to width ratios (compact tension specimen) against the load under plane stress condition. The finite element analysis (using ANSYS) outcomes ( KI and J‐integral) have good agreement with the theoretical value.